Intra-tropical migration and wintering areas of Fork-tailed Flycatchers (Tyrannus savana) breeding in Sao Paulo, Brazil - Jahn, Alex E. [UNESP]; Seavy, Nathaniel E.; Bejarano, Vanesa [UNESP]; Guzman, Marcela Benavides [UNESP]; Carvalho Provinciato, Ivan Celso [UNESP]; Pizo, Marco A. [UNESP]; MacPherson, Maggie (Soc Brasileira Ornitologia, 2016)
Fork-tailed Flycatchers (Tyrannus s. savana) breed from central to southern South America from September to January, migrating to northern South America to spend the non-breeding season. However, little is known of the migratory routes, rate, and timing of migration of those that breed in Brazil. In 2013, we attached light-level geolocators to breeding Fork-tailed Flycatchers breeding in Sao Paulo State. Data for six male flycatchers recaptured in 2014 indicates that they exhibited two fall migration strategies. Some individuals migrated northwest to the wintering grounds (primarily Colombia, Venezuela and northern Brazil), while others first spent several weeks in southwestern Brazil before going to the wintering grounds. Mean fall migration rate was 69 km/day (+/- 13.7) during 59 (+/- 13.2) days. Some flycatchers moved during winter, using more than one winter area. Flycatchers initiated spring migration in July and migrated southeast to the breeding grounds at a mean rate of 129 km/day (+/- 19.0) during 27 (+/- 2.8) days. A detailed understanding of the annual cycle of South America's migratory birds is essential to evaluating theoretical questions, such as the evolution of their life history strategies, in addition to applied questions, such as explanations for changes in population size, or their role as disease vectors.
Keywords: austral; Cerrado; Itirapina; molt; Neotropical